Desarrollo de un sensor capacitivo para la medición de la penetración de iones de cloro en estructuras porosas - diseño para estructuras de concreto reforzado (2016)
"The specific objectives are: 1. Understand the phenomena of corrosion induced by chloride ingress, and identify the importance Of chloride assessment. 2. Identify the design requirements of a chloride sensor by performing a literature review about existing methods and technologies for detecting and quantifying chlorides to recognize their advantages and drawbacks. 3. Develop a new technique capable to detect the presence of chloride ions into concrete based on the electrical characterization of commercial monocalcium aluminate (CA) in presence of chloride ions. 4. Design and build a new chloride sensor by considering: geometry, materials (e.g., selective layer, matrix of sensor, etc.), construction process, durability, stability, and procedures for measuring. 5. Evaluate the device suitability by determining the device performance (e.g., sensitivity, limit of detection, and time response) of coplanar and parallel measurements"